2014
DOI: 10.1021/la501945t
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Zwitterionic Surfactant on Limestone Measured with High-Performance Liquid Chromatography: Micelle–Vesicle Influence

Abstract: Herein is presented a new methodology to determine the static adsorption of a zwitterionic surfactant on limestone in three different aqueous media [high-performance liquid chromatography (HPLC) water, seawater, and connate water] with the use of HPLC at room temperature and 70 °C. The results showed that, in both HPLC water and seawater, the surfactant adsorption followed a monolayer Langmuir tendency. In contrast, for connate water, the surfactant presented a new adsorption profile, characterized by two regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 24 publications
0
39
1
Order By: Relevance
“…It could be found that, with the increase of NaCl concentration, equilibrium adsorption of DSB on limestone decreased. Our ndings were opposite to the results of Nieto-Alvarez et al 15 In the study of Nieto-Alvarez et al 15 with the increase of water salinity, equilibrium adsorption increased. Cocamidoproyl hydroxysultaine (in the study of Nieto-Alvarez et al) has a similar structure and property to DSB used in our study.…”
Section: Effect Of Inorganic Salt On Adsorptioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It could be found that, with the increase of NaCl concentration, equilibrium adsorption of DSB on limestone decreased. Our ndings were opposite to the results of Nieto-Alvarez et al 15 In the study of Nieto-Alvarez et al 15 with the increase of water salinity, equilibrium adsorption increased. Cocamidoproyl hydroxysultaine (in the study of Nieto-Alvarez et al) has a similar structure and property to DSB used in our study.…”
Section: Effect Of Inorganic Salt On Adsorptioncontrasting
confidence: 99%
“…meant that a small amount of inorganic salt could favor the formation of vesicles, while further addition of inorganic salt would inhibit the formation. In Nieto-Alvarez et al's study, 15 the results showed that formation of vesicles was responsible for the decrease of adsorption at high surfactant concentrations. Different from Nieto-Alvarez et al's study, the formation of vesicles occurred at low inorganic salt, so no adsorption decrease was detected in our study.…”
Section: Effect Of Dsb Aggregation On Adsorptionmentioning
confidence: 91%
See 1 more Smart Citation
“…A Thermo Acclaim surfactant plus HPLC column (Thames Restek Ltd., UK) of dimensions 3 mm×150 mm and particle size of 5 m was used in this study. This type of column is compatible with aqueous and organic phases and is appropriate for the analysis of a wide variety of surfactant types at high salinity [32][33][34]. HPLC measurements were performed in an Agilent 1290 Infinity UHPLC.…”
Section: Porous Medium Preparationmentioning
confidence: 99%
“…Here, an optimized HPLC-ELSD [22][23][24][25][26] method was successfully developed for the analysis of complex multicomponent surfactant formulations that cannot be analyzed by conventional titration methods due to their interactions. Second, the adsorption of each component and surfactant blend was systematically studied on differently charged mineral surfaces.…”
Section: Introductionmentioning
confidence: 99%